Monitoring of selective residue collect and soap production in the Instituto Verde Vida, Aribiri River Region – Vila Velha – ES - Veríssimo de Oliveira, Glayton; Palomé, Lucas; Marques Carvalho, Rafael; Gegenheimer Gouveia, Tiago; Kapiche Alonso, Michelle; Grisostomo Lima Santos, Mariana; Brígida Soares, Ana; do Carmo, Ana Paula; Coutinho Endringer, Denise; do Vale Oliveira, Rosinalia; Dias, Mauro Cesar (Guará Journal, 2016)
In Brazil, the generation of municipal solid waste is approximately 60.8 million tons/year, with about 10% of these are launched in the oceans, rivers, streams and vacant lots, which has caused a number of environmental impact problems on these ecosystems. With the approval of the specific Law on the National Policy on Solid Waste, the waste management is now directed to the whole society’s responsibility. The Instituto Verde Vida (IVV) performs the selective residue collect, reducing the risk of generation of high pollution waste and contributing to sustainability. Community members interact during the activities carried out by the IVV, which promotes the Solidarity Economy and, subsequently falls within the concept of Green Chemistry. The aim of this work was to monitor the selective collect of solid waste and residual oil frying (ROF) during the 2014-2015 period occurred at the Instituto Verde Vida, located in the Aribiri river region, Vila Velha, ES, Brazil. Furthermore, as an extension work promoted by the Instituto Federal do Espírito Santo Campus Vila Velha (Ifes Vila Velha, ES, Brazil), the ROF collected was used as a base for soap making, where a group of manufacturers has been formed and its activity monitored in terms of production quality control